2010
DOI: 10.11646/zootaxa.2335.1.2
|View full text |Cite
|
Sign up to set email alerts
|

A new genus of oak gallwasps, Kinseyella Pujade-Villar & Melika, with a description of a new species from Mexico (Hymenoptera: Cynipidae: Cynipini)

Abstract: A new genus of a cynipid oak gallwasp, Kinseyella (Hymenoptera: Cynipidae: Cynipini) is described from Mexico. Diagnostic characters and generic limits of the new genus are discussed in details. A new species, Kinseyella quercusobtusata is described, which induces galls on leaves of Quercus obtusata, an endemic Mexican oak. One earlier known species from Mexico was transferred to the newly established genus, Kinseyella lapiei (Kieffer), comb. nova. Diagnostic characters for separation of two species are also g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 22 publications
0
10
0
3
Order By: Relevance
“…En la región Neártica se han detectado a 87 especies y 15 en la región Neotropical (Pénzes et al, 2012). En México, se han registrado Ceroptres, Synophromorpha y Synergus (Pujade-Villar et al, 2008).…”
Section: Resultados Y Discusiónunclassified
“…En la región Neártica se han detectado a 87 especies y 15 en la región Neotropical (Pénzes et al, 2012). En México, se han registrado Ceroptres, Synophromorpha y Synergus (Pujade-Villar et al, 2008).…”
Section: Resultados Y Discusiónunclassified
“…However, because of the relatively poor taxon sampling in their analysis and the lack of convincing support values for the clades within the Cynips group, they refrained from proposing formal taxonomic changes in Cynips group. Pujade-Villar et al (2010) described one new genus from Mexico ( Kinseyella ) related to Cynips group and suggested that the neartic genera Antron and Besbicus were erroneously synonymized to Cynips by Melika and Abrahamson (2002). …”
Section: Discussionmentioning
confidence: 99%
“…The Nearctic fauna is the richest, with approximately 700 species in 22 genera (Melika and Abrahamson 2002). In México, 170 species are known trophically associated with more than 30 oak species (Kinsey 1936(Kinsey , 1937a(Kinsey ,b, 1938Melika et al 2009Melika et al , 2011Nieves-Aldrey et al 2012;Pujade-Villar et al 2009, 2010, 2011a,b, 2012, 2013a, while approximately 150 Quercus species are known (Govaerts and Frodin 1998), of which 86 are considered endemic (Nixon 1998, Zavala 1998.…”
Section: Introductionmentioning
confidence: 99%